Hak Waris Transeksual Ditinjau Dari Hukum Waris Adat Masyarakat Minangkabau (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
With the rapid development of globalization, there are people who have the desire to change their own gender or what is usually called transsexual. Transsexualism can happen to someone due to environmental factors and hormonal factors. This phenomenon raises problems in all legal dimensions, one of which concerns inheritance for transsexuals. In this writing, normative juridical research methods are used because this research examines library materials to find certainty about Minangkabau customs. In Indonesia itself, it still recognizes customs which are the inheritance of customs. As in Minangkabau custom, it is still motivated by the values and norms of the Islamic religion. It is known that the Islamic religion does not accept the existence of transsexuals, so Minangkabau customs also reject these transsexuals. This writing  to find out, explain and analyze transsexual inheritance in Minangkabau customs.